Performance of islamic religious counselors in executing counseling function during the Covid-19 pandemic - Rini Laili Prihatini; Eri Rustamaji (Jurnal Ilmu Dakwah, 2022)
Purpose - This paper presents the results of the performance analysis of Islamic Religious Counselors in 6 provinces on the island of Java during the COVID-19 pandemic. This analysis needs to be conducted considering that on one hand, there are quite complex community problems that need to be managed by Religious Counselors, while on the other hand the number of Islamic Religious  Counselors, especially those with the Civil Servants (PNS) status, is not proportional to the large and diverse number of target audiences.Method - This study uses a quantitative approach with a survey method. The research sample was 96 Functional Islamic Religious Counselors (PAIF/PNS) which were collected using simple random sampling techniques in 6 provinces, namely DKI Jakarta, Banten, West Java, Central Java, Special Region Yogyakarta, and East Java. Data collection techniques were carried out by observing and distributing online questionnaires through google forms. Descriptive statistics and inferential statistics (Spearman rank correlation) were used for analyzing data.Result - The results showed that: 1) the level of social support, situational support, and the performance of the counselors were classified as moderate, and 2) social support and situational support were positively and significantly related to the performance of the Islamic religious counselors in carrying out their counseling function during the COVID-19 pandemic. This means that the higher the social support and situational support, the better the performance of the religious instructor in carrying out the counseling function during the COVID-19 pandemic, and vice versa.Implication - The level of performance of Islamic religious instructors can be used as a consideration to determine the right training or self-development program for religious counselors in carrying out their functions properly.Originality - This paper is the first research report that analyzes the performance of functional Islamic religious instructors, covering 6 provinces on the island of Java, in carrying out their outreach functions during the Covid-19 pandemic.  ***Tujuan - Makalah ini menyajikan hasil analisis kinerja Konselor Agama Islam di 6 provinsi di Pulau Jawa selama pandemi COVID-19. Analisis ini perlu dilakukan mengingat di satu sisi permasalahan masyarakat cukup kompleks yang perlu dikelola oleh Penyuluh Agama, sementara di sisi lain banyaknya Konselor Agama Islam, khususnya yang berstatus Pegawai Negeri Sipil (PNS). tidak sebanding dengan jumlah khalayak sasaran yang besar dan beragam.Metode – Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Sampel penelitian adalah 96 Pendamping Agama Islam Fungsional (PAIF/PNS) yang dikumpulkan dengan menggunakan teknik simple random sampling di 6 provinsi yaitu DKI Jakarta, Banten, Jawa Barat, Jawa Tengah, Daerah Istimewa Yogyakarta, dan Jawa Timur. Teknik pengumpulan data dilakukan dengan observasi dan penyebaran kuesioner online melalui google form. Statistik deskriptif dan statistik inferensial (korelasi peringkat Spearman) digunakan untuk menganalisis data.Hasil - Hasil penelitian menunjukkan bahwa: 1) tingkat dukungan sosial, dukungan situasional, dan kinerja konselor tergolong sedang, dan 2) dukungan sosial dan dukungan situasional berhubungan positif dan signifikan dengan kinerja konselor agama Islam. dalam menjalankan fungsi penyuluhan di masa pandemi COVID-19. Artinya, semakin tinggi dukungan sosial dan dukungan situasional, maka semakin baik kinerja penyuluh dalam menjalankan fungsi penyuluhan di masa pandemi COVID-19, begitu pula sebaliknya.Implikasi - Tingkat kinerja penyuluh agama Islam dapat dijadikan pertimbangan untuk menentukan program pelatihan atau pengembangan diri yang tepat bagi penyuluh agama dalam menjalankan fungsinya dengan baik.Orisinalitas - Tulisan ini merupakan penelitian pertama yang menganalisis kinerja fungsional penyuluh agama Islam yang mencakup 6 provinsi di Pulau Jawa dalam menjalankan fungsi dakwahnya di masa pandemi Covid-19.